Diversity analysis of fruit traits of 105 peach germplasm resources in Xinjiang - LI Dan; BAI Lixia; TANG Zhuoyue; YANG Kanghui; YANG Lu; CHENG Ping (Guoshu xuebao, 2025)
[Objective] The study aimed to deeply understand the variability and diversity of fruit traits of different peach [Prunus persica (L.) Batsch] germplasm resources and screen excellent peach germplasm resources. [Methods] A total of 105 peach germplasm resources were used as experimental materials, and 22 descriptive traits were observed by visual observation. Nine fruits with good fruit shape and no mechanical damage were selected. The quantitative trait indexes were measured. The variability and diversity of 22 phenotypic traits and 14 quantitative traits of the fruits were analyzed. The fruit traits of 105 germplasms were comprehensively evaluated and sorted by principal component analysis, and were classified by cluster analysis. [Results] The 22 diversity index (H') of description traits ranged from 0.627 to 1.502, the diversity index of the fruit apex shape was the highest (1.502), followed by the color of the fruit skin (1.300), and the diversity index of the kernel smoothness was the lowest (0.627). The 14 coefficient of variation (2.34%-74.12%) and diversity index (1.783-2.079) of quantitative type traits showed a large range, indicating that peach fruit types were abundant. The highest coefficient of variation was hardness with skin and hardness without skin, which were 74.12% and 57.28%, respectively. The highest hardness with skin was Huayu (11.88 kg·cm-2), the smallest was Qi dry misuri (0.50 kg·cm-2), and the lowest coefficient of variation of edible rate was 2.34%. The fruit side diameter was the largest (2.079) and the edible ratio was the smallest (1.783). A total of 4 principal components were extracted by principal component analysis, and the cumulative contribution rate reached 80.887%, indicating that these 4 principal components could represent most of the information of 16 indicators. From the selected eigenvalues and eigenvectors of the principal components of the 16 fruit traits of the 105 peach germplasms, we could see that the first principal component was mainly composed of single fruit weight, transverse diameter, lateral diameter, peeled hardness and peeled hardness, reflecting the size and storage and transportation ability of the fruits. The second principal component was mainly composed of the fruit shape index, fruit shape and fruit top shape, and the third principal component was mainly composed of the cover color depth and coloring degree, which reflected the appearance quality of the fruits. The fourth principal component was mainly composed of the soluble solids content, reflecting the flavor of the fruits. The cluster analysis of the 105 peach germplasm resources showed that there were significant differences in the characteristics of different groups. When the Euclidean distance was 60, it could be divided into 5 groups. The first group included 24 germplasm resources, mainly Xinjiang germplasm, most of them were mid- late maturing germplasm, showing the characteristics of small single fruit weight, low hardness, high soluble solids content and rich aroma. The group Ⅱ contained 25 germplasm resources, which were characterized by the early maturity, medium single fruit weight, low hardness, high soluble solids content and strong aroma. The group Ⅲ contained 32 germplasm resources, which were characterized by the early maturity, large single fruit weight, high hardness and high soluble solids content. The group Ⅳ contained 21 germplasm resources, most of them were mid- late maturity germplasm, showing the characteristics of large single fruit weight, high hardness and high soluble solids content. The group Ⅴ contained 3 germplasm resources, which were mid-late maturing germplasm. The single fruit weight and hardness of this group were significantly higher than those of other groups, but the soluble solids content was lower. [Conclusion] The variation types of fruit traits in jujube germplasm resources were abundant and the diversity index was high (H'). The principal component combination cluster analysis screened out high soluble solid content, storage and transport resistant germplasm Zhongyoujinguan, Zhongyoujinhong, Ruiguang 28, big fruit type and storage and transport resistant germplasm Huayu, Zaojiu Bao, high soluble solid content, rich aroma, and intolerant germplasm for storage and transportation LG- 9#, LG- 8#, LG- 13#, Hongguang 1. The study would provide reference for breeding and extension of peach varieties in Xinjiang.